ECONOMIC IMPACT OF THE RESEARCH AND DEVELOPMENT OF A COMPUTER SYSTEM FOR FOREST MANAGEMENT OF PINUS SPP. - Rodrigues de Alencar, Júnia; Herruzo, Casimiro; Hoeflich, Vitor Afonso; Batista de Oliveira, Edilson (Science & Technology Journals, 2004)
The objective of this research was to evaluate the economic benefits derived from public investments in research and development of a computer system. This system, SISPLAN, is designed to perform simulations on growth and productivity for afforestation and reforestation of Pinus in southern Brazil. Criteria can be generated for production planning and reforest management, thereby reducing the uncertainties associated mostly with forest activity planning. This is especially important in cases of technical-scientific knowledge that are not incorporated in the production means, because they are generated during field-research activities involved with different aspects of the forest. The method consists in identifying the costs and economic benefits derived from the generation, utilization, and maintenance of the SISPLAN technology. The framework of this research provides the estimated economic impact, using the cost-benefit technique. Utilization of this system generates information that contributes to improving efficiency in the productive sector and effectiveness in public policies. Economic gains to Brazil were estimated at 77.2 million in 1997 (net present value), with a cost-benefit ratio of 55.7. This indicates that the research is an attractive economic investment.